Differential career well-being among Indonesian guidance and counseling teachers - Syahril, M Fiqri; Krismona, Elwas Berdha; Nasution, Salsabila; Jannah, Raudha Nur Hidayah Al (Universitas Negeri Yogyakarta, 2025)
The research aims to determine the career well-being profile of guidance and counseling teachers in Indonesia. This study employed a quantitative approach with a comparative design to examine differences in the career well-being of guidance and counseling teachers based on years of service. An analysis of variance (ANOVA) was used to determine whether significant differences in career well-being existed among groups with different lengths of service. In addition, descriptive statistics were used to provide an overview of the levels of career well-being among guidance and counseling teachers in Indonesia. The population in this research was guidance and counseling teachers in Indonesia. The sample consisted of 1,000 guidance and counseling teachers who were selected using simple random sampling; therefore, each member of the population had the same opportunity to be chosen without bias. Data were collected using a career well-being scale based on Coetzee's theory, developed by the researchers. The instrument was tested for validity and reliability using the Rasch Model and was then distributed via Google Forms. Data analysis used percentage-based statistical formulas. The career well-being difference test showed a Sig. value of 0.00, which means guidance and counseling teachers had differences in career well-being based on their work experience. This research concludes that the longer the work experience of guidance and counseling teachers, the higher their level of career well-being. This study recommends analyzing other factors that influence the career well-being of guidance and counseling teachers in Indonesia, such as educational background, work environment, organizational support, and workload, to obtain a more comprehensive picture.